The Motif of “Awakening” in the Poetic Texts of Turkic Literature (Eurasian Journal of Philology Science and Education, 2025)
In the poetic tradition of the Turkic peoples, the theme of “awakening” occupies an important place as a fundamental value that revives historical memory, cultural identity and collective consciousness. This theme reflects both personal spiritual enlightenment and the struggle for renewal and liberation that peoples have experienced throughout history. In the poetic heritage of the Central Asian steppe culture up to the present day, awakening finds various manifestations: in epics - as a revival of the nation, in folk poetry - as social solidarity, in modern literature - as a strengthening of the individual. The Jadid movement, which arose in the 19th and 20th centuries, contributed to the formation of a solid ideological basis for the theme of awakening in Turkic literature. While the poets of that period conveyed ideas of modern education, national self-awareness and cultural reform through metaphors and symbolism, the motif of awakening became a literary symbol of the liberation of both the individual and society. In Soviet literature, this theme often served to maintain public consciousness through symbolic and allegorical expressions.Poets from Turkey, Azerbaijan, Kazakhstan, Kyrgyzstan, Tatarstan, Uyghurs and other Turkic peoples interpreted awakening as a process of national rebirth and individual discovery of inner truth. This study examines the historical, cultural and aesthetic aspects of the theme of awakening through selected poetic works from different regions.Keywords: awakening, Turkic literature, Jadidism, national consciousness, poetic texts.